Research on the Influence of Center Distance Error Distribution Model on Dynamic Characteristic of Split Torque Transmission System - Jingwei Ding; Guanghu Jin; Rupeng Zhu (Jixie chuandong)
In order to improve the load sharing performance and transmission stability of the split torque transmission system， aiming at a single input double output gear torque transmission system， three kinds of linkage center distance error calculation models of a single-input double-output gear split torque transmission system are established based on the idea of symmetry， synchronous change and follow-up. The projection calculation formula of the error on the meshing line is derived， and the influence of distribution of three kinds of linkage center distance error on the system load sharing and dynamic load coefficient is studied. The results show that the center distance error has little influence on the load sharing coefficient and dynamic load coefficient. The deflection angle under three different calculation models has a great influence on the system load sharing coefficient and dynamic load coefficient， especially the synchronous and follow-up change modes. From the calculation results， using the symmetrical error distribution model， there is a large choice of distribution space for error， which can be used to obtain the good dynamic performance of the cylindrical gear transmission system.